BY THE SECRETARY OF ELECTRONIC SCHEDULING USING VISUAL BASIC 6.0 PT. BERSAMA ABADI - Lukisjn Lumban Gaol; Susi Wagiyati, MM (Jurnal Sistem Informasi, 2003)
It describes the application of scientific writing language into the Visual Basic secretarial work activities, where all their activities is very helpful in accomplishing tasks of a leader. One of the activities can be scheduled properly. This application program makes a working agenda of the database is always up to date so that data can be added, deleted and modified. In order to produce a better view, then this program is built using Microsoft Visual Basic 6.0. In addition  to this in writing also explained about the making of the application program.